The Correlation of Antibacterial Peptides Concentration in Umbilical Cord Blood and Early Onset Sepsis in Preterm Infants - Miao, Jiayu; Ren, Zhuxiao; Zhong, Zhicheng; Xu, Fang; Wang, Jianlan; Yang, Jie (Frontiers in Pediatrics, 2022)
Umbilical cord blood from singleton preterm infants was collected during delivery, and the concentration of LL37 was measured. CRP, WBC, PLT and MPV were determined within 3 days after birth. The differences in LL37, CRP, WBC, PLT and MPV levels between the two groups were compared. Pearson correlation method was used to analyze the correlation between these factors. The early individually value of each detected index for early-onset sepsis was analyzed by ROC curve.The level of LL37 in umbilical cord blood of sepsis group was significantly higher than those of in control group (383.85±46.71 vs 252.37±83.30 ng/ml). Meanwhile, the levels of CRP, WBC and MPV in sepsis group were significantly higher than those of in control group (CRP:5.73±4.19 vs 2.50±2.77 mg/L; WBC: 13.47±12.35 vs 6.83±3.55×109/L; MPV: 11.20±1.11 vs 8.90±0.68 fL), the level of PLT was significantly lower than those of in control group (PLT: 161.00±38.51 vs 241.50±49.85×109/L) (P < 0.05). Pearson correlation analysis showed that the expression of LL37 was negatively correlated with PLT level(r = -0.9347, P < 0.0001), and positively correlated with MPV level ((r =0.9463 , P < 0.0001). ROC curve analysis showed that the area under curve of LL37 for diagnosis of early-onset sepsis was 0.875, the prediction probability was 0.7, the sensitivity was 90.0% and the specificity was 80.0%.